Implementation Of Financial Module And Cost Control Management In Syariah Erp To Improve Company Profitability - Dewi, Arlinta Prasetian; Asyarie, Adimas Agus; Anis, Muhammad; Asiyah, Binti Nur; Subagyo, Rohmat (Westscience Press, 2025)
This study aims to evaluate the implementation of Financial and Cost Control Management modules in a sharia-based Enterprise Resource Planning (ERP) system and analyze its impact on the company's profitability level. In a Sharia ERP system, financial management and cost control must be in accordance with the principles of transparency, efficiency, and compliance with sharia rules. This study was conducted through a literature study approach, by collecting and reviewing various relevant literature on Sharia Enterprise Resource Planning (ERP), financial management, and cost control strategies in companies based on sharia principles. The results of the study indicate that the implementation of the Financial and Cost Control Management modules in Sharia ERP can improve the efficiency of transaction recording, financial transparency, and budget and operational cost control, thus having an impact on increasing the company's profitability. The implementation of this system also supports the company's compliance with sharia-based financial regulations, which in turn contributes to increasing investor confidence and strengthening the company's competitiveness in the halal industry ecosystem. Thus, the implementation of Sharia ERP integrated with the Financial and Cost Control Management modules can be an effective strategy in improving the financial performance of sharia companies